(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
This study aims to study how the use of organic fertilizers affects the vegetative growth of king grass (Pennisetum purpureophoides) in Bangko Campus IV, West Halmahera. For this experiment, a Complete Randomized Model (RAL) was used, which had four treatments and four replicates. P0 (no organic fertilizer), P1 (50% organic fertilizer), P2 (75% organic fertilizer), and P3 (100% organic fertilizer). The variables Height, length, width, branch length, and stem diameter of the plant were observed. The results of the study showed that organic fertilizer treatment actually affected the increase in vegetative growth of king grass. The application of 100% organic fertilizer (P3) produces the best vegetative growth with a plant height of 155.4 cm, leaf length (strands) of 85, with a leaf length (strand) of 3.1 cm, leaf width (strand) of 3.1 cm, internode length of 18.7 cm, and stem diameter of 10.6 mm, organic fertilizer can increase the availability of nutrients in the earth and improve the physical, chemical, and biological properties of the soil. With a length times the width of 3.1 cm each, while the length of the segment is 18.7 cm, and the diameter of the stem is 10.6 mm, organic fertilizer can be used as a source of nutrient availability in the soil and improve the physical, chemical, and biological properties of the soil..